Environmental management system and ISO 14000 in textile industry - sustentability as trend - Alencar, José Luciano Sobreira de; Simoni, Júlio Henrique; Fiorelli, Mariana Natale; Neto, Generoso De Angelis (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Advent of the environmental Problem that arose at around the middle of the 20th century reflected in the posture of the organizations in relation to their productive process and their interaction with the Ecosystem. The demands of society and authorities for a sustainable development pressured organizations towards the utilization of better environmental practices that were socially just and economically viable. The answer for that was to integrate into the admistrative system of the organizations an Environmental management that would aggregate the value of their strategies and would satisfy the desires of all parties involved. The ISO 14000 follows international standards for the certification of an Environmental management System providing guidelines and methodology to help the organizations accomplish their responsibilities for a more sustainable planet. The textile industry is an example of pro-active attitudes and initiative in the face of the challenges in the search for a sustainable development of its segment as it tries to integrate in its productive line a cleaner process that is ecologically innovative.